A chronology for moat construction and sedimentation at Chengziya – A late Neolithic urban settlement in Eastern China. (February 2020) - Su, Kai; Zhu, Chao; Sun, Bo; Jin, Guiyun
Highlights: 13 radiocarbon dates and 22 OSL dates were achieved from a moat sequence at Chengziya site. Bayesian chronological models were built to determine the cultural boundaries at the site, and confirmed a continuous occupation from Longshan to Yueshi period. In human constructed environment such as a moat, dating samples should favor the radiocarbon ones from strictly defined archaeological context. Abstract: As the site that defines the Longshan Culture in China, Chengziya has produced few absolute dates over decades of research. The excavation of moat structures in the northwestern corner of the site in 2017 provided a new opportunity to collect materials for dating from secure archaeological contexts. Thirteen radiocarbon dates and twenty-two OSL (optically stimulated luminescence) dates were obtained from a stratigraphic sequence and evaluated within a Bayesian interpretive framework to assess the timing and temporality of occupation at the site, from the Longshan through Zhou periods. The model shows that the Longshan occupation at Chengziya started in 2520 – 2130 cal. BC (95.4%) and ended in 2245 – 2020 cal. BC (95.4%). The Yueshi occupation started in 2170 – 1960 cal. BC (95.4%), supporting the argument for continuous occupation from the Longshan to Yueshi period at Chengziya. The early transitional period between the Longshan and Yueshi contradicts the understanding of local archaeologists, which can be explained in terms of new way of thinking archaeological cultures in this region, dating materials and new findings at the site. Discussions also touch on how the taphonomic environment could influence the dates and the chronological model.